Любовь с двадцать первого взгляда: повесть / Таня Воробей - Воробей Таня (Мой первый роман, 2004)
Экземпляры: ф. 4 (20110211) / Инвентарный номер: 96893 / Цена: 26.80 / Авт.знак: В 75 / ББК: 84(2Рос=Рус)6